2015
DOI: 10.1260/0309-524x.39.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Reference Cases for Verification of Operation and Maintenance Simulation Models for Offshore Wind Farms

Abstract: Due to lack of operating experience in the field of offshore wind energy and large costs associated with maintaining offshore wind farms, there is a need to develop accurate operation and maintenance models for strategic planning purposes. This paper provides an approach for verifying such simulation models and demonstrates it by describing the verification process for four models. A reference offshore wind farm is defined and simulated using these models to provide test cases and benchmark results for verific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 12 publications
1
87
0
Order By: Relevance
“…These eleven different studies were performed by and on behalf of different-often government-constituencies from 2007 through 2015 (see Table 1 below for a high-level presentation of the eleven studies). Similar to earlier conclusions by e.g., Blanco [42] (p. 1374) and Dinwoodie et al [72] (p. 8), it was determined as part of this research that the studies are very different in their fundamental assumptions and methodology including key parameters such as OWF capacity in MW and WTGrating. It was also concluded that none of the studies have a clear logistics definition nor does any single study break down logistics as a separate OpEx/O&M cost item.…”
Section: The Logistics Share Of Offshore Wind Operations and Maintenasupporting
confidence: 71%
“…These eleven different studies were performed by and on behalf of different-often government-constituencies from 2007 through 2015 (see Table 1 below for a high-level presentation of the eleven studies). Similar to earlier conclusions by e.g., Blanco [42] (p. 1374) and Dinwoodie et al [72] (p. 8), it was determined as part of this research that the studies are very different in their fundamental assumptions and methodology including key parameters such as OWF capacity in MW and WTGrating. It was also concluded that none of the studies have a clear logistics definition nor does any single study break down logistics as a separate OpEx/O&M cost item.…”
Section: The Logistics Share Of Offshore Wind Operations and Maintenasupporting
confidence: 71%
“…Martin et al (2016). This experience is also being used to validate O&M models, as described by Dinwoodie et al (2014). These studies generally agree that further operational experience will increase confidence in inputs to O&M models, such as failure rates, thereby increasing the reliability of the outputs, e.g.…”
Section: Oandm Modelsmentioning
confidence: 86%
“…The properties of each type of failure, including cost to repair, estimated maintenance action time, number of technicians required, and the weight of spares/tools can be found in Table S1 in the Supplementary Material. The cost of repairs and annual service were adapted from Dinwoodie et al [26]. Turbine locations and types of maintenance action required on each turbine are shown in Figure 2.…”
Section: Model Inputsmentioning
confidence: 99%